Structure sensitivity of the low-temperature dehydrogenation of perhydro dibenzyltoluene on supported platinum nanoparticles - Mahayni, Yazan; Maurer, Lukas; Auer, Franziska; Hutzler, Andreas; Wasserscheid, Peter; Wolf, Moritz (Catalysis: Science and Technology, 2024)
In this study, the structure sensitivity of the dehydrogenation reactions of the commonly used liquid organic hydrogen carrier (LOHC) molecules perhydro dibenzyltoluene (H18-DBT) and perhydro benzyltoluene (H12-BT) is investigated. We focus on the hydrogen release at moderate reaction temperatures, which is particularly relevant to enable heat integration of the LOHC dehydrogenation process with, for example, high-temperature fuel cells for an enhanced overall efficiency. To determine the most suitable platinum nanoparticle size with the highest surface specific productivity, a colloidal approach was used for the synthesis of Pt/Al2O3 catalysts with well-defined nanoparticle sizes. These catalysts were used in the dehydrogenation reactions of H18-DBT and H12-BT in the temperature ranges of 250-280 °C and 220-240 °C, respectively. A structure sensitivity was identified in both cases, which becomes particularly prominent at lower reaction temperatures. This is attributed to the overall slower reaction kinetics and the amplified differences of the adsorption strength on different surface sites. A maximum in surface specific productivity was found for catalysts with a Pt nanoparticle size of 2.6 nm for H18-DBT and 2.3 nm for H12-BT dehydrogenation. It is assumed that the observed structure sensitivity is mainly due to an optimal surface composition of the nanoparticles with an ideal balance between strongly adsorbing corner and edge sites and less active terrace sites. At low temperatures, desorption from low coordinated sites is limiting for nanoparticles below 2.3 nm, while the increasing share of terrace sites in nanoparticles larger than 2.7 nm reduces the overall productivity of the catalyst due to their lower specific activity. This behavior becomes less pronounced at higher temperatures. The dehydrogenation of H12-BT was even shown to be rather structure insensitive at 240 °C.
CRIS-Team Scopus Importer:2024-08-23